White matter microstructure alterations in systemic lupus erythematosus: A preliminary coordinate-based meta-analysis of diffusion tensor imaging studies. (October 2021) - Zhou, Cong; Dong, Man; Duan, Weiwei; Lin, Hao; Wang, Shuting; Wang, Yuxin; Zhang, Yujia; Shi, Jiameng; Liu, Shirui; Cheng, Yuqi; Xu, Xiufeng; Xu, Jian
Background: Systemic lupus erythematosus is often accompanied with neuropsychiatric symptoms. Neuroimaging evidence indicated that microstructural white matter (WM) abnormalities play role in the neuropathological mechanism. Diffusion tensor imaging (DTI) studies allows the assessment of the microstructural integrity of WM tracts, but existing findings were inconsistent. This present study aimed to conduct a coordinate‐based meta‐analysis (CBMA) to identify statistical consensus of DTI studies in SLE. Methods: Relevant studies that reported the differences of fractional anisotropy (FA) between SLE patients and healthy controls (HC) were searched systematically. Only studies reported the results in Talairach or Montreal Neurological Institute (MNI) coordinates were included. The anisotropic effect size version of signed differential mapping (AES-SDM) was applied to detect WM alterations in SLE. Results: Totally, five studies with seven datasets which included 126 patients and 161 HC were identified. The pooled meta-analysis demonstrated that SLE patients exhibited significant FA reduction in the left striatum and bilateral inferior network, mainly comprised the corpus callosum (CC), bilateral inferior fronto-occipital fasciculus (IFOF), bilateral anterior thalamic projections, bilateral superior longitudinal fasciculus (SLF), left inferior longitudinal fasciculus (ILF), and left insula. No region with higher FA was identified. Conclusions: Disorders of the immune system might lead to subtle WM microstructural alterations in SLE, which might be related with cognitive deficits or emotional distress symptoms. This provides a better understanding of the pathological mechanism of microstructural brain abnormalities in SLE.